Economic Impacts of Real Estate in Nepal - Chandra Prasad Dhakal, (Interdisciplinary Journal of Management and Social Sciences, 2024)
Real estate is one of the important economic sectors of Nepal around 90 national properties covered by real estate. In this context, the study analyzes the how real estate play's role in national economy and economic activities in Nepal. Main objective of this study is to analyze the economic impacts on real estate business in Nepal. The study follows the qualitative research design and used both primary and secondary source of the data. Primary data were collected from in depth interview with respondents and secondary data were collected through library research. Books, articles, journals, government reports and thesis were the main source of secondary data. Conclusion of this is based on the analysis of both primary and secondary data. Traditional concept about property, global influence, high flow of remittance and government policy play importance role in real estate business. Each of the economic activities of Nepal is influenced by real estate business.